HIBAH WASIAT (TESTAMENT) DAN PELAKSANAANNYA - Bambang Hermoyo; Shinta Rukmi Budiastuti (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
Inheritance by testament (ad testamento) is a deed that contains a person's statement about what he or she wants for wealth after he dies. The testament or will that is made must be in the form of a deed and notarial deed. This means that making a will requires the name of a public official to ratify the will. If it is not made before a notary, then the testator who wrote his own will can submit the will to the notary after it has been signed. As long as the testator has not died, the will can be changed or revoked by him. In contrast to an agreement that requires the agreement of the parties involved, a will is one-sided which means a statement of the will of the heir, or does not require the approval of the heirs. To protect the rights of the heirs, the heir cannot ignore the absolute rights of the heirs themselves when the inheritance is divided by a testament that exceeds the absolute rights of the heirs (in the event that there are legal heirs)